Pengembangan Bahan Ajar Berbasis HOTS Berbantuan Google Sites Materi Ekosistem dan Perubahan Lingkungan di SMA - Ida Ayu Putu Lisya Dewi; Ida Bagus Putu Arnyana; Ajeng Purnama Heny; I Made Sutajaya; I Wayan Sukra Warpala (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to develop and evaluate the feasibility of a Higher Order Thinking Skills (HOTS)-based learning material for the topic of ecosystems and environmental change for Grade X senior high school students. The research employed a Research and Development (R&D) approach following the ADDIE development model, which includes the stages of analysis, design, development, expert validation, and practicality testing. Product validity was assessed by experts in content, language, and media, while practicality was examined through questionnaires administered to three biology teachers and 34 Grade X students at SMA Negeri 1 Sawan. Data were analyzed using descriptive quantitative methods. The validation results indicate a Gregory Validity Coefficient of 1, signifying a very high level of validity. Practicality tests yielded scores of 91.66% from teachers and 90.34% from students, both categorized as highly practical. The final product is a HOTS-based learning material integrated with Google Sites, featuring interactive content, digital worksheets, instructional videos, educational games, and online assessments. The study concludes that the developed learning material is valid, practical, and has the potential to enhance student engagement and critical thinking skills in alignment with the demands of 21st-century learning.